2011
DOI: 10.1007/s10404-011-0859-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative particle dynamics simulation of field-dependent DNA mobility in nanoslits

Abstract: The dynamics of DNA molecules in highly confined nanoslits under varying electric fields are studied using dissipative particle dynamics method, and our results show that manipulation of the electrical field can strongly influence DNA mobility. The mobility of DNA l scales with electric field E as l ¼ l H À k 1 e ÀE=E c : And the data points for different DNA lengths finally approach each other in strong fields, which suggest that the sensitivity to chain length is almost lost. To explain the unusual field-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…While DPD is not as computationally efficient as lattice Boltzmann simulations, it is a more flexible method that does not suffer from the numerical instability associated with many lattice Boltzmann applications. DPD facilitates the simulation of complex fluid systems on physically interesting and important length and time scales, including bio-particle and DNA filtering systems [56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…While DPD is not as computationally efficient as lattice Boltzmann simulations, it is a more flexible method that does not suffer from the numerical instability associated with many lattice Boltzmann applications. DPD facilitates the simulation of complex fluid systems on physically interesting and important length and time scales, including bio-particle and DNA filtering systems [56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, dissipative particle dynamics (DPD) has proven capabilities for capturing the dynamic and rheological properties of simple and complex fluids, and thus may be deployed to solve the proposed questions at an acceptable accuracy and an affordable computational cost. So far DPD has been successfully applied to investigate biomolecular behavior, such as DNA moving in nanoslits ( 23 ) and endocytosis of liposomes ( 24 ). In this study, we use DPD to gain insight into the interactions between the EG and the glycocalyx of passaging RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…And its study has been substantially motivated by the recent development in nanotechnology. Although being ubiquitous in fields such as membrane separation, nano‐confined catalysis, energy conversion, and DNA sequencing, nanofluidics still has many unsettled questions. For instance, Fornasiero et al and Holt et al found that the flow rates of pressure‐driven fluids in the sub‐2‐nm carbon nanotube pores are about three orders‐of‐magnitude greater than those predicted by the no‐slip Hagen–Poiseuille (H‐P) relation.…”
Section: Introductionmentioning
confidence: 99%